Sporadic Congenital Hyperplasia of Interstitial Cell of Cajal of Rectum as a Cause of Chronic Constipation - Alimohammad Bananzadeh (Shiraz University of Medical Sciences, 2013)
Gastrointestinal stromal tumors (GIST) are the usual primary mesenchymal neoplasms of the GI tract. Interstitial cells of Cajal (ICCs) are intestinal pacemaker cells that instigate peristalsis in the stomach and intestine, and are measured to be precursors of GIST. We are reporting a 17 year old boy with chronic constipation since childhood and a huge rectum in abdominal radiography, who underwent exploratory laparotomy, resection of huge rectum and construction of sigmoid colostomy. Pathology report was "Hyperplasia of Interstitial Cells of Cajal".